SCHOOL STRATEGIES IN STRENGTHENING STUDENT RESILIENCE IN DISASTER-PRONE AREAS - Siti Irene Astuti Dwiningrum; Khirjan Nahdi; Aswasulasikin Aswasulasikin; Dyah Respati Suryo Sumunar; Rukiyati Rukiyati; Ebny Sholikhah (Jurnal Cakrawala Pendidikan, 2020)
Resilience is needed by students who live in disaster-prone areas. With strong resilience, students can implement disaster mitigation. This study aims to describe the profile of students' resilience and the strategies carried out by students in strengthening personal resilience. The mixed method research approach was conducted on a research population of SMA/SMK in Lombok Regency, specifically North Lombok, East Lombok, and West Lombok. The respondents were 779 people from 10 schools in disaster-prone areas determined by the Slovin formula. Student resilience profiles were explored according to Reivich and Shatte. Data on how teachers increase students’ resilience were obtained from a focus group discussion (FGD) with 20 teachers from 10 schools. The results of the research prove that the personal resilience profile of students in Lombok from the seven aspects is still not optimal, which is not enough to form resilience personalities (less than 60%). This study affirms that personal resilience is essential in building school resilience to provide a massive contribution to education and disaster mitigation. Regarding recommendations for schools to increase student resilience, it can be done by increasing resilience resources, strengthening social support, having resilient teachers, building resilient school, all aspects of which must work systemically and synergistically.